Nouveaux apports sur l’archéologie du littoral de Guyane : de la préhistoire à la conquête - Martijn M. van den Bel (Journal de la Société des Américanistes)
In French Guiana, structured archaeological research only started in the early 1970s. Its results have been synthesized by Stéphen Rostain twenty year later. The proposed chronocultural framework focused mainly on the coastal plains situated between the Oyapock and Kourou Rivers for the Late Ceramic Age, between AD 900 and 1700. This study presents the condensed results of six recent compliance archaeological excavations. They permit us firstly to enrich the existing framework of this overseas French department by presenting new data concerning the Archaic and Early Ceramic Ages, hitherto undiscovered episodes, substantially enlarging this framework. Furthermore, new elements concerning the Late Ceramic Age renew certain aspects, notably concerning funerary practices, ceramic complexes and food consumption of the prehistoric Amerindians.